(untitled) (Swiss Medical Weekly, 2019)
As a result of epidemic levels of obesity and diabetes mellitus, nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) will contribute to increases in the liver-related disease burden in Switzerland. A Markov model was built to quantify fibrosis progression among the NAFLD and NASH populations, and predict disease burden up to 2030. Long-term trending of NAFLD prevalence was based on changes in the prevalence of adult obesity. Published estimates and surveillance data were applied to build and validate the model projections. The prevalence of NAFLD increased up to 2030 in tandem with projected increases in adult obesity. By 2030, there were an estimated 2,234,000 (1,918,000–2,553,000) NAFLD cases, or 24.3% (20.9–27.8%) of the total Swiss population (all ages). Increases in NASH cases were relatively greater than NAFLD cases. Incident cases of advanced liver disease are projected to increase by approximately 40% by 2030, and incident NAFLD liver deaths to increase from 580 deaths in 2018 to 820 deaths in 2030. Continued growth in obesity, in combination with an aging population, will result in increasing number of cases of advanced liver disease and mortality related to NAFLD and NASH. Slowing the growth in obesity and metabolic syndrome, along with future potential therapies, are required to reduce liver disease burden.